LITHOPHAGA (DIBERUS) BISULCATA A MYTILID BORER CAUSING DAMAGE TO THE COMMERCIALLY IMPORTANT GASTROPOD SHELLS - Appukkuttan, K K (Indian Journal of Fisheries, 2011)
The marine bivalves, capable of burrowing into corals, submerged rocks, concrete structures, sandstones and into moUuscan shells, belong mainly to the genera Botula, Lithophaga, Tridacna, Venurupis, Petricola, Aloides, Platyodon, Hiatella, Gastrochaena, Pholas, Barnea, Zirfaea, Pholadidea, Panitella, Parapholas, Diplothyra and Jouannetia. Among these, Lithophaga is the most important genus from the point of view of destruction to corals and commercially important shells